A halophilic metalloprotease from Salinivibrio sp. YH4 and its application in antioxidant peptide production - Liu, Dan; Xiao, Yuyang; Wei, Yingying; Xie, Maojia; Huang, Yu; Gan, Chaoyu; He, Hailun (Frontiers in Microbiology, 2025)
PurposesThis study aimed to develop a sustainable strategy for valorizing protein-rich industrial by-products into functional antioxidants using halophilic biocatalysts, addressing environmental challenges and the demand for bioactive compounds.MethodsA moderately halophilic bacterium, Salinivibrio sp. YH4, was isolated from Yuncheng Salt Lake and identified as S. costicola (99% 16S rRNA homology). The extracellular protease EYHIII? was purified and biochemically characterized for thermal/pH stability, halotolerance, and substrate specificity. Fish collagen hydrolysates generated by EYHIII were evaluated for antioxidant capacity via 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl, and peroxyl radical scavenging assays. Cellular bioactivity was validated in high glucose-stressed human umbilical vein endothelial cells (HUVECs), analyzing ROS levels and antioxidant enzyme activity.ResultsEYHIII was a thermostable (5060°C) and alkaliphilic (pH 7.59.5) M4-family metalloprotease. The enzyme retained >80% activity under high salinity conditions (1 M NaCl) and exhibited strict substrate specificity for hydrophobic residues (Phe/Leu) at the P1’ position. It efficiently hydrolyzed both soluble and insoluble collagens. Fish collagen hydrolysates generated by EYHIII demonstrated potent antioxidant activity, scavenging 33.53 ± 3.30% of DPPH radicals and 45.55 ± 3.00% of hydroxyl radicals at 3 mg/mL, with a peroxyl radical absorbance capacity of 1.69 ± 0.07 mmol TE/g. In human umbilical vein endothelial cells (HUVECs), the hydrolysate reduced high glucose-induced reactive oxygen species (ROS) to baseline levels at 200 μg/mL. It also significantly upregulated antioxidant enzymes compared to damaged controls: superoxide dismutase (SOD, 103.55%), catalase (CAT, 110.96%), and glutathione peroxidase (GSH-Px, 135.79%) (all P < 0.05).ConclusionsThis study highlighted Salinivibrio sp. YH4 and its protease EYHIII as a sustainable platform for converting collagen waste into high-value antioxidants. These findings addressed both environmental pollution and the growing demand for functional bioactive compounds. The results underscored the potential of halophilic biocatalysts in advancing circular economy strategies for protein resource utilization.